Fear of Missing Out Fuels Impulsive Buying Behavior in Gen Z: Rasa Takut Ketinggalan Mendorong Perilaku Pembelian Impulsif pada Gen Z - Rinonce, Elvil Manik; Jannah, Miftakhul (Universitas Muhammadiyah Sidoarjo, 2025)
This research is motivated by technological advances that cause a shift in marketing from offline stores to e-commerce. The ease with which consumers make purchases in e-commerce makes them vulnerable to impulsive buying tendencies, including Gen Z. This study aims to determine the effect of fear of missing out (FoMO) on impulsive buying tendencies in Gen Z. This study uses a non-experimental quantitative method approach. The subjects in this study amounted to 240 Gen Z students in the X department at University X in Surabaya City, Indonesia, with criteria aged 17–22 years, and they are active users of e-commerce. The sampling technique used is purposive sampling. The instruments used in this study were the Fear of Missing Out Scale and the Impulsive Buying Scale. The data analysis technique uses a simple linear regression test with the program JASP 0.18.3 for Windows. The results of a simple linear regression test show a significant level of p-value = 0.001 < 0.05, which means there is an influence of fear of missing out on impulsive buying, so the hypothesis proposed in this study can be accepted. Other results show the R-value is 0.359 with an R square value or the coefficient of determination (R2) of 0.129. This value shows the effect of the fear of missing out on impulsive buying by 12%. There is a positive influence of the fear of missing out variable on the impulsive buying variable, meaning that Gen Z is more likely to engage in impulsive purchases when their fear of missing out is greater. Highlights: FoMO Drives Impulse Buying – Higher fear of missing out increases impulsive purchases in Gen Z. Moderate Influence – FoMO explains 12% of impulsive buying tendencies based on R² value. Significant Effect – Regression analysis confirms a strong link (p = 0.001) between FoMO and impulse buying. Keywords: Fear of Missing Out, Impulsive Buying, Gen Z